2016
DOI: 10.1021/jacs.6b07680
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Enzymatic Targets of Transcriptional Activators via in Vivo Covalent Chemical Capture

Abstract: The network of activator protein-protein interactions (PPIs) that underpin transcription initiation is poorly defined, particularly in the cellular context. The transient nature of these contacts and the often low abundance of the participants present significant experimental hurdles. Through the coupling of in vivo covalent chemical capture and shotgun LC-MS/MS (MuDPIT) analysis, we can trap the PPIs of transcriptional activators in a cellular setting and identify the binding partners in an unbiased fashion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…[26] UAA 1 was site-specifically incorporated into Gal4 and yeast cells were grown with either glucose or galactose as ac arbon source.U V irradiation revealed that Gal4 directly contacts the core enzymatic unit of the Snf1 complex, ah eterotrimeric kinase, which is known to play an important role in gene activation for carbon-source sensing,aswell as its exchangeable subunit Gal83, which is important for the nuclear localization of the kinase complex. [26] UAA 1 was site-specifically incorporated into Gal4 and yeast cells were grown with either glucose or galactose as ac arbon source.U V irradiation revealed that Gal4 directly contacts the core enzymatic unit of the Snf1 complex, ah eterotrimeric kinase, which is known to play an important role in gene activation for carbon-source sensing,aswell as its exchangeable subunit Gal83, which is important for the nuclear localization of the kinase complex.…”
Section: Delineating Protein Interactomes In Changed Physiological Stmentioning
confidence: 99%
“…[26] UAA 1 was site-specifically incorporated into Gal4 and yeast cells were grown with either glucose or galactose as ac arbon source.U V irradiation revealed that Gal4 directly contacts the core enzymatic unit of the Snf1 complex, ah eterotrimeric kinase, which is known to play an important role in gene activation for carbon-source sensing,aswell as its exchangeable subunit Gal83, which is important for the nuclear localization of the kinase complex. [26] UAA 1 was site-specifically incorporated into Gal4 and yeast cells were grown with either glucose or galactose as ac arbon source.U V irradiation revealed that Gal4 directly contacts the core enzymatic unit of the Snf1 complex, ah eterotrimeric kinase, which is known to play an important role in gene activation for carbon-source sensing,aswell as its exchangeable subunit Gal83, which is important for the nuclear localization of the kinase complex.…”
Section: Delineating Protein Interactomes In Changed Physiological Stmentioning
confidence: 99%
“…In one study, direct PPIs between the transcriptional activator Gal4 and the Snf1/AMPK complex were pinpointed at a specific stress-response gene promoter in living cells. 18 This revealed that Gal4 makes two contacts within the Snf1/AMPK complex. One is with the enzymatic core unit, Snf1/AMPK, a kinase that phosphorylates both DNA-bound repressor proteins to facilitate their removal and the tail of RNA polymerase II to stimulate its activity.…”
mentioning
confidence: 96%
“…For example, aziridinoadenosines have been shown to work as activity‐based probes for a range of methyltransferases and form stable, tight‐binding bisubstrate adducts . Previous studies with chemical tagging and shotgun proteomics might be amenable for IsoLAIT adaptation . IsoLAIT can be broadly applicable and similarly successful for other enzyme systems, particularly those catalyzing group transfer and with multiple substrates, such as glycosyltransferases and kinases.…”
Section: Figurementioning
confidence: 99%